Koncepcja poety wedlug teorii typowych romantykow angielskich i polskich - Ordona, Edmund (University of Ottawa (Canada), 1952)
Abstract not available.
Keywords: Literature, Modern.; Literature, Slavic and East European.; Literature, English.